1957
DOI: 10.1149/1.2428626
|View full text |Cite
|
Sign up to set email alerts
|

Electrodeposition of Lead from the Pyrophosphate Bath

Abstract: not Available.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
7
0

Year Published

1957
1957
2014
2014

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 1 publication
3
7
0
Order By: Relevance
“…However, variations in composition with current density, pH, and temperature have been reported by Fink and Lah (3), and Pletenew and Kusnezowa (15). Work done in this laboratory has shown a similar constancy of composition during the deposition of alloys of nickel with tin (16), iron (10), and zinc (17), and of iron with zinc (18) from pyrophosphate solutions.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations
“…However, variations in composition with current density, pH, and temperature have been reported by Fink and Lah (3), and Pletenew and Kusnezowa (15). Work done in this laboratory has shown a similar constancy of composition during the deposition of alloys of nickel with tin (16), iron (10), and zinc (17), and of iron with zinc (18) from pyrophosphate solutions.…”
Section: Discussionmentioning
confidence: 71%
“…Physicochemical measurements have shown that the metal ion concentration (g ion/l) and instability constant for the pyrophosphate complexes are of the order of 10 -9 for nickel (8) and 10-' for cobalt (11). Ammonium citrate was added as a bath constituent since it was beneficial from the view point of buffering of solution, limiting cathode current density, cathode efficiency, and deposit composition range Its concentration was based on previou~ studies on nickel (8) and cobalt (9) plating from the pyrophosphate bath.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The basic solution for the electrodeposition of P-PbO 2 on a lead substrate was prepared by adding lead nitrate to a sodium pyrophosphate solution, then a complex, Na 2 [Pb(P 2 O 7 )], was formed. 12 The interaction of the lead substrate with the deposition solution at the rst stage of electrodeposition is discussed in detail in part II of the ESI. † This initial stage was considered to be of great importance.…”
mentioning
confidence: 99%